The Effect of Childhood Trauma on Borderline Personality Features: The Mediating Role of Dissociation and the Moderating Role of Metacognitive Beliefs - Abbaszadeh, Parisa; Mahmoud Alilou , Majid; Hashemi Nosratabad, Touraj (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study aimed to investigate the effect of childhood trauma on borderline personality features, with a particular focus on examining the mediating role of dissociation and the moderating role of metacognitive beliefs among adults in Tehran.Methods and Materials: This study employed a cross-sectional correlational design using structural equation modeling. The statistical population consisted of adults residing in Tehran during the 2025–2026 academic year, from whom 420 participants were selected through multistage cluster sampling. Data were collected using the Childhood Trauma Questionnaire (CTQ), Borderline Personality Features Scale (BPFS), Dissociative Experiences Scale-II (DES-II), and Metacognitions Questionnaire-30 (MCQ-30). Data analysis was conducted using SPSS-27 and AMOS-24. Pearson correlation analysis was used to examine associations among variables, while structural equation modeling was employed to test the hypothesized moderated mediation model.Findings: The results revealed significant positive associations among childhood trauma, dissociation, metacognitive beliefs, and borderline personality features. Childhood trauma significantly predicted dissociation (β = .63, p < .001) and borderline personality features (β = .38, p < .001). Dissociation significantly predicted borderline personality features (β = .49, p < .001) and partially mediated the relationship between childhood trauma and borderline personality features. Bootstrap analysis confirmed the significance of the indirect effect (β = .31, 95% CI [.24, .40]). Metacognitive beliefs significantly predicted borderline personality features (β = .29, p < .001) and moderated the relationship between childhood trauma and borderline personality features (β = .18, p < .001), indicating that higher maladaptive metacognitive beliefs strengthened the impact of childhood trauma on borderline pathology.Conclusion: The findings suggest that childhood trauma exerts both direct and indirect effects on borderline personality features. Dissociation functions as a key psychological mechanism through which traumatic childhood experiences contribute to borderline pathology, while maladaptive metacognitive beliefs intensify this relationship.